Neosataria, replacement name for Sataria Annandale, 1920 (Mollusca: Gastropoda: Bithyniidae), preoccupied by Sataria Roewer, 1915 (Arachnida: Opiliones: Sclerosomatidae) - Kulkarni, Siddharth; Khot, Rahul (Zootaxa, 2015)
The family Bithyniidae is represented in tropical Asia by the following genera, Bithynia, Digonistoma, Mysorella, Parabithynia, Emmericiopsis, Hydrobioides, Parafossarulus, Pseudovivipara, Sataria and Wattebladia (Dudgeon 1999; Pyron & Brown 2015).